Tele-oncology in the COVID-19 Era: The Way Forward? - Shirke, Manasi Mahesh (Trends Cancer, 2020)
COVID-19 has had a devastating impact on the care of cancer patients. Thus, tele-oncology has become a necessity to improve cancer care. Several organisations have issued guidelines for its use during COVID-19. Despite certain shortcomings, tele-oncology has great potential to help cancer patients during COVID-19 and in the future.